Perbedaan Status Pemberian ASI Eksklusif terhadap Perubahan Panjang Badan Bayi Neonatus (Media Kesehatan Masyarakat Indonesia, 2018)
Exclusive breastfeeding is the first and foremost of natural food for baby because breastfeeding canfulfill the baby’s needs for energy and nutrients the baby even during the first 6 months of life.The Ministry ofHealth in 2015 targets for exclusive breastfeeding 80%. In 2013, the highest coverage of exclusive breastfeedingin Bangka Belitung is Pangkalpinang (59,4%)So this study aimed to assess the difference between the status ofexclusive breastfeeding to changes the body lenght of neonates in RSUD Depati Hamzah Pangkalpinang.This typeof research was a cohort with a sampel of 34 mothers who gave birth in RSUD Depati Hamzah Pangkalpinangin June-July 2015. The research instrument used a questionnaire and length board scaleThe independent t-testaimed to see the difference in weight and measurement results body lenght of neonates in each group observationstatus every 7 consecutive days as long 28 day.The results showed that mothers who non exclusive breastfeedingis 55,9% (19 people) and exclusive breastfeeding is 44,1% (15 people). The average of lenght neonates givenexclusive breastfeeding 1 month is greater was 10,87 cm than non exclusive breastfeeding only was 8,53 cm.Theresults showed that there was no difference significanthy of mean in lenght between exclusive breastfeeding andnon exclusive breastfeeding.
Keywords: ASI eksklusif; neonatus; panjang badan